Batik Tambun Bungai Penciptaan Motif Lokal Untuk Kejatidirian Eknonomi Kreatif Kalimantan Tengah - Nawung Asmoro Girindraswari; Utari Yolla Sundari; Muh.Andis Hidayatullah; Muhamad Romadoni (IPM2KPE, 2024)
This research aims to create local batik motif. This research was focused on creating local Tambun Bungai batik motifs for the creative economic identity of Central Kalimantan Province in supporting SDGs in regional development. This research uses a design creation approach that is implemented on fabric using a digital batik printing process. The design creation research methods involves the following steps. (1) identification (2) research (3) idea formulation (4) prototype (5) selection (6) implementation (7) evaluation. The results yield are typical Tambun Bungai batik which has its own uniqueness, inspired by the richness of the natural landscape, traditional art and has bold color patterns that convey a strong impression of the philosophical values ​​inherent in Central Kalimantan batik motifs as well as being an effective regional promotional media. Keywords: Batik, Dayak, Creative economy, Central Kalimantan